NURSING STUDENTS’ PERCEPTION ON THE USE OF ROLE-PLAY TECHNIQUE IN LEARNING ENGLISH-SPEAKING SKILL - Susiana Kaban; Youlanda Sari (Bajang Institute, 2022)
Role Play is a simulation of the behavior of the person being played, which aims to train students in dealing with real situations; intensive practice of spoken language; and provide opportunities for students to develop communication skills. The purpose of this study was to investigate the perceptions of nursing students of STIKes Flora on the use of the role play method in developing communication skills in English. The subjects of this research are 4th semester students of the Flora Nurses STIKes Study Program for the Academic Year 2021/2022. This is a qualitative research where data is obtained using (1) observation method (2) documentation method (2) interview method, data is analyzed through the following steps ; organizing data, reducing data, presenting data and drawing conclusions. From the results of the study it was found that there are four benefits that can be obtained from the application of the roleplay method in improving speaking skills: the role play method makes students understand the lecture material more easily, helps students to be more confident in speaking in English, provides a lot of experience that can be applied in reality as a nurse who works in the hospital and encourage fun athmosphere in learning process